Staphylococcus Lugdunensis Vascular Aortic Graft infection: A report of first case (Bangladesh Critical Care Journal, 2021)
Staphylococcus lugdunensis has been reported to cause a wide variety of serious infections to include infective endocarditis, peritonitis and osteomyelitis. This report describes our patient who developed aorto bifemoral graft infection with Staphylococcus lugdunensis not previously described in the literature.Bangladesh Crit Care J September 2021; 9 (2): 116-117